IMPROVING STUDENT'S VOCABULARY MASTERY BY USING THE FLY SWATTER GAME IN SEVENTH GRADE OF SMP N 31 MEDAN - Br Purba, Roh Dearni; Napitupulu, Fenty Debora; Sidabutar, Usman (Jurnal Teknologi Mesin UDA, 2025)
The research aimed to find out improving students’ vocabulary mastery by using fly swatter game. This research was conducted by using Classroom Action Research (CAR). The subject of this research was grade VII-1 of SMP Negeri 31 Medan 2023/2024 academic year, which consisted of 31 students. The object of this research was to improve the students’ vocabulary mastery through fly swatter game. This researcher was conducted in two cycles which each consists’ of planning, acting, observing, and reflecting. Data was obtained by observation, then students’ vocabulary scores on the pre-test, post-test, and questionnaire. Based on the result of this research showed that there was a development in the student’s vocabulary mastery; it can be seen from the mean score of the pre-test was 54.3, the mean score of post-test 1 was 74.8, and the mean score of pot- the test cycle 2 was 85.4. In addition, 5 students (16.12%) passed the Minimum Mastery Criterion (KKM) in the pre-test. Meanwhile, in cycle 1, there were 21 students (67.7%) who passed the Minimum Mastery Criterion (KKM), and it gained which was in the post-test cycle 2, 27 students (87%) who passed the Minimum Mastery Criterion (KKM), the criteria of success was achieved. Then, the result of the questionnaire showed that there was an improvement in positive responses in the teaching-learning process of vocabulary through the fly swatter game. The mean of pre-questionnaire was 43.18%. Then, the mean of post-questionnaire was 93.5%. It improved 49.32%. Furthermore, the results of observation showed that the students were motivated in the teaching-learning process during the implementation of the fly swatter game.